Emerging drugs for the treatment of myasthenia gravis. (3rd July 2021) - Menon, Deepak; Urra Pincheira, Alejandra; Bril, Vera
ABSTRACT: Introduction : Advances in understanding the immune pathomechanisms in myasthenia gravis (MG) allow for the development of novel targeted immune therapies. By working at specific points in the immunopathogenesis, these agents have the potential to provide rapid and efficacious responses compared to conventional immunosuppressive therapy (IST), addressing unmet needs and consequently are a research priority. Areas covered : This paper reviews the advances in MG treatment modalities with their scientific rationale. A search of clinicaltrials.gov and a literature search of PubMed from January 2015 to the end of June 2021 was done using the search terms: MG, treatment, immune targets to obtain information on recent developments of complement inhibitors, FcRn receptor inhibitors, direct and indirect B cell inhibitors, CAR and CAAR- T cell therapy, and hematopoietic stem cell transplantation. Specific agents in various phases of clinical development, evidence from ongoing trials and potential roadblocks are examined. Expert opinion : Despite several promising novel agents, existing data as to the timing of initiation and duration of treatment, long-term safety profile and utility in certain patient subsets are limited and require further research. Despite these considerations, the future of MG treatment is transitioning from broad-spectrum IST toward precise, target-driven and personalized immunotherapy.